Application of puberty animation media to improve student independence class VI elementary school - Rosyadi, Ajib; Dewi Wulandari, Murfiah; Rahayu, Fitri (JURNAL PENDIDIKAN DASAR NUSANTARA, 2023)
The purpose of this research is to find out the application of puberty animation learning media in increasing the independence of class VI students at SDN 9 Purwodadi in 2021/2022. The research method used was classroom action research (PTK) with a total sample of 32. The data collection method used observation, tests, interviews, and documentation with the percentage results pre-cycle average achievement level of 44.32%, cycle I with an average achievement level of 48.7, and cycle II with an average achievement level of 79.36% had an increase. This is evidenced by the increasing percentage of the number of students independence in the process of teaching and learning activities before and after being given action